Guided Note Taking Strategy with PowerPoint to Enhance Vocational Students' Interest in Economic Actions, Motives, and Principles - Umi Hidayati; Hariyono Hariyono (STAI Miftahul Ula Nganjuk, 2024)
Vocational education often faces challenges due to low student interest in subjects like economics. This study investigates the effectiveness of using PowerPoint presentations to enhance the learning interest of Class X students in SMK Negeri 2 Nganjuk, particularly in understanding economic actions, motivations, and principles. A pre-experimental design with a one-group pretest-posttest was employed, involving 34 students selected through random sampling. The study utilized a learning interest questionnaire, and data were analyzed using a paired t-test. The results revealed a significant increase in student interest, with a t-count value of 5.5334 exceeding the t-table value of 1.668. Key indicators such as student happiness, engagement, interest, and attention all showed improvements, with an average increase from 32.76 to 76.62. These findings highlight the effectiveness of PowerPoint-guided teaching methods in fostering greater interest in vocational education. The study suggests the need for ongoing teacher competency development and further exploration of the long-term effects on academic achievement and job readiness.